Agricultural wages and food prices in Egypt: a governorate-level analysis for 1976-1993 - Datt, Gaurav; Olmsted, Jennifer (International Food Policy Research Institute, 1998)
The trend in real agricultural wages in Egypt is described well by an inverted U-shaped curve with a peak around 1985. But the rise and fall of real wages masks a complex dynamic process by which nominal wages adjust in response to changes in food prices. We use governorate-level panel data for 1976–1993 to explore the nature of this adjustment process. Our results indicate that nominal wages adjust slowly. There is a significant negative initial impact of rising food prices on real wages, though wages do catch up in the long run.